Manual for Streets. - (:unkn) unknown (Thomas Telford Publishing, 2007)
The manual provides a clear framework for the use of local systems and procedures; it also identifies the tools available to ensure that growth and change are planned for and managed in an integrated way. Research carried out in the preparation of Manual for Streets indicated that many of the criteria routinely applied in street design are based on questionable or outdated practice. For example, it showed that, when long forward visibility is provided and generous carriageway width is specified, driving speeds tend to increase. This demonstrates that driver behaviour is not fixed; rather, it can be influenced by the environment. MfS addresses these points, recommending revised key geometric design criteria to allow streets to be designed as places in their own right while still ensuring that road safety is maintained. MfS is clear that uncoordinated decision-making can result in disconnected, bland places that fail to make a contribution to the creation of thriving communities. It recommends that development teams are established to negotiate issues in the round and retain a focus on the creation of locally distinct, high-quality places. Where high levels of change are anticipated, designers and other stakeholders are encouraged to work together strategically from an early stage. MfS also recommends the use of tools such as masterplans and design codes.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Straßenbau; Parken; Handlungsempfehlung; Radverkehrsführung; Fahrradinfrastruktur; Radverkehrsanlage; Richtlinie; Verkehrswegeausbau; Handbuch